IMPROVING TAXATION AND SOCIAL PAYMENTS AS IMPORTANT COMPONENTS OF THE STATE BUDGET - Zh.O. Lukpanova; A.C. Dairabaeva; А.К. Orazgalieva (Academic Journal of Physical and Chemical Sciences, 2019)
The authors draw attention to the problem of inefficiency of taxation, as there is a numerous tax inspectorate, tax police, departments of the Internal Affairs Directorate to combat economic crimes, and yet the result of the work leaves much to be desired. Lists the problems of unskilled staff of these bodies, the inability to competently conduct support, audit, often many legal entities and individuals easily escape responsibility for tax evasion. However, the state budget includes revenues and expenditures and is a unity of the main parts of the financial system: government spending, taxes, state credit and a separate economic category, reflecting the financial relations of the state with individuals and legal entities regarding the redistribution of national income when using the budget fund, which is intended financing of national economy, social and cultural events, the needs of public administration and us.